Aqueous matte coating agent, laminate, and method for manufacturing the laminate.
Patent Information
- Application Number
- JP2025058875
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0019】 本開示によれば、作業性および環境性に優れ、塗膜を硬化させた際にはマット性および耐摩擦性に優れたマットコート層を形成するための水性マットコート剤、およびそれを用いて形成される積層体を提供することができる。
Smart Images

Figure 2026166121000001 
Figure 2026166121000002 
Figure 2026166121000003
Abstract
Description
TECHNICAL FIELD
[0001] The present disclosure relates to an aqueous matte coating agent, a laminate, and a method for producing the laminate.
BACKGROUND ART
[0002] In recent years, in the field of packages using paper base materials represented by paper containers, for the purpose of imparting durability and aesthetic properties to printed matter, extensive research has been conducted on applying coating agents after printing color inks on various base materials. Regarding paper container packages, when displayed at retail stores after printing, there are cases where glossiness is required for aesthetic purposes, and cases where matte properties are required. Matte properties are also referred to as delustering properties, and in particular, demand for printed matter with a delustering effect has been increasing in recent years.
[0003] Conventionally, solvent-based matte coating agents containing a resin, a matting agent and a solvent have been commonly used as matte coating agents for paper container packages, for the purpose of imparting a high-grade feel through high matte properties. In general, solvent-based matte coating agents provide a high matting effect as the solvent component volatilizes from the coating film in the post-printing drying step, which reduces the volume of the coating film and results in the matting agent being oriented on the coating film surface, but they are inferior in workability and environmental performance. Furthermore, in solvent-based matte coating agents, the solid content of the ink fluctuates as the solvent component volatilizes during coating film formation, which raises concerns about viscosity fluctuations during coating film formation, risks of environmental pollution caused by the volatilized solvent, and the like.
[0004] Accordingly, in recent years, solvent-free active energy ray-curable matte coating agents with improved workability and environmental performance have been developed. Furthermore, demand for aqueous matte coating agents has been increasing from the viewpoints of workability and environmental performance.
[0005] Patent Document 1 discloses an aqueous ink composition for surface printing that can impart an excellent matte finish to the surface of articles, particularly plastic molded products, and is resistant to gloss return. This composition comprises a binder resin, a matting agent, and an aqueous medium, wherein the binder resin is at least one selected from the group consisting of aqueous urethane resin, aqueous acrylic resin, and aqueous acrylic urethane resin, and the matting agent contains an extender pigment and organic particles.
[0006] Patent Document 2 discloses an aqueous coating agent that provides a soft, velvet-like or suede-like texture to the substrate of printed materials such as paper containers, with the aim of enhancing their luxurious feel and appeal. This coating agent contains urethane resin and styrene-acrylic resin, and the urethane resin is in the form of beads with a specified particle size. The content of the urethane resin and acrylic resin is also specified.
[0007] Patent Document 3 discloses an aqueous ink composition that yields a coating film with excellent properties such as substrate adhesion, abrasion resistance, water abrasion resistance, heat resistance, and scratch resistance, and contains two types of acrylic emulsion resins with different acid values, and either or both titanium dioxide and precipitated barium sulfate. It also discloses that a curing agent and resin beads may be further included. [Prior art documents] [Patent Documents]
[0008] [Patent Document 1] Japanese Patent Publication No. 2023-087626 [Patent Document 2] Japanese Patent Publication No. 2009-227707 [Patent Document 3] Patent No. 7567081 [Overview of the project] [Problems that the invention aims to solve]
[0009] The technology disclosed in Patent Document 1 only provides specific examples using aqueous urethane resin and aqueous acrylic resin separately. Therefore, it is unclear whether a combination of different resin types will maintain a matte finish while also providing scratch resistance.
[0010] The technology disclosed in Patent Document 2 combines urethane resin beads with styrene-acrylic resin, and does not combine different types of resins. Since styrene-acrylic resin is a relatively hard resin, the flexibility of the coating layer is poor, and sufficient abrasion resistance cannot be obtained. Furthermore, the technology disclosed in Patent Document 2 forms a coating film by heat fusion of styrene-acrylic resin with an acid value, which provides a soft feel, but does not provide sufficient abrasion resistance.
[0011] The technology disclosed in Patent Document 3 uses two types of acrylic emulsion resins with different acid values. However, because acrylic resins themselves tend to form hard coatings, it becomes difficult to obtain flexibility in the coating, and sufficient abrasion resistance cannot be achieved. Furthermore, in the technology disclosed in Patent Document 3, resin beads are used to improve the abrasion resistance, water abrasion resistance, and scratch resistance of the coating, and a coating with a matte finish is not provided.
[0012] One of the objectives of this disclosure is to provide an aqueous matte coating agent for forming a matte coating layer that is excellent in workability and environmental friendliness, and has excellent matte properties and abrasion resistance when the coating film is cured, and a laminate formed using the same. [Means for solving the problem]
[0013] Some embodiments of this disclosure are shown below. <1> A water-based matte coating agent comprising an emulsified acrylic resin, an emulsified urethane resin, resin fine particles, an aqueous medium, and a curing agent. <2> The acid value is 40 mgKOH / g or less and the hydroxyl value is 20 mgKOH / g or more relative to the total mass of the emulsion-type acrylic resin and the emulsion-type urethane resin. <1> The water-based matte coating agent described above. <3> The emulsion-type acrylic resin, the emulsion-type urethane resin, and the resin fine particles are provided as a first liquid, and the curing agent is provided as a second liquid. <1> or <2> The water-based matte coating agent described above.
[0014] <4> The mass ratio of the emulsion-type urethane resin to the total amount of the emulsion-type acrylic resin and the emulsion-type urethane resin is 30 to 90% by mass. <1> from <3> A water-based matte coating agent as described in any of the following. <5> The total of 100 parts by mass of the emulsion-type acrylic resin and the emulsion-type urethane resin contains 30 to 100 parts by mass of the resin fine particles. <1> from <4> A water-based matte coating agent as described in any of the following. <6> The absolute value of the difference between the acid value of the emulsion-type acrylic resin and the acid value of the emulsion-type urethane resin is 100 or less. <1> from <5> A water-based matte coating agent as described in any of the following.
[0015] <7> The average particle size of the aqueous matte coating agent is 0.1 to 10 μm. <1> from <6> A water-based matte coating agent as described in any of the following. <8> The average particle size of the resin fine particles is 1 to 5 μm. <1> from <7> A water-based matte coating agent as described in any of the following. <9> Further containing polyolefin wax particles, <1> from <8> A water-based matte coating agent as described in any of the following.
[0016] <10> The average particle size of the polyolefin wax particles is 0.3 μm or less. <9> The water-based matte coating agent described above. <11> The average particle size of the polyolefin wax particles is 0.1 μm or less. <9> The water-based matte coating agent described above. <12> The curing agent includes an isocyanate-based curing agent. <1> from <11> A water-based matte coating agent as described in any of the following.
[0017] <13> For paper substrates, <1> from <12> A water-based matte coating agent as described in any of the following. <14>A laminate comprising a paper base material and a matte coat layer, wherein the matte coat layer is a cured film of the aqueous matte coating agent according to any one of <1> to <13>.
[0018] <15>A method for producing a laminate, comprising a step of mixing a first liquid and a second liquid to obtain an aqueous matte coating agent, and a step of flexographically printing the aqueous matte coating agent on a base material, wherein the aqueous matte coating agent is the aqueous matte coating agent according to any one of <1> to <13>.
Effects of the Invention
[0019] According to the present disclosure, it is possible to provide an aqueous matte coating agent that is excellent in workability and environmental performance, and forms a matte coat layer excellent in matting property and abrasion resistance when the coating film is cured, and a laminate formed using the same.
Modes for Carrying Out the Invention
[0020] Several embodiments of the present disclosure will be described in detail below, but the description of the constituent elements described below is an example of the embodiments of the present disclosure, and the present disclosure is not limited to these contents as long as it does not exceed the gist thereof.
[0021] In the present disclosure, (meth)acrylic and (meth)acrylate mean methacrylic and / or acrylic, and methacrylate and / or acrylate, respectively. In addition, (meth)acryloyl means methacryloyl and / or acryloyl. In some cases, the aqueous matte coating agent is simply referred to as a matte coating agent.
[0022] In this disclosure, unless otherwise specified, the weight-average molecular weight (Mw) is a measurement value in polystyrene equivalent obtained by gel permeation chromatography. For example, the weight-average molecular weight can be measured using the Shodex GPC System-21 gel permeation chromatography system manufactured by Resonaq Corporation. GPC is a liquid chromatography system that separates and quantifies substances dissolved in a solvent based on the difference in their molecular size. Tetrohydrofuran is preferred as the solvent, and the determination of the weight-average molecular weight is preferred in polystyrene equivalent. Further details can be obtained by following the methods disclosed in the examples.
[0023] In this disclosure, unless otherwise specified, the glass transition temperature (Tg) is a measurement taken by differential scanning calorimeter (DSC). The glass transition temperature is defined as the midpoint between the endothermic start temperature and the end temperature based on the glass transition in the DSC curve. For details, it can be measured according to the method disclosed in the examples.
[0024] In this disclosure, viscosity is measured at 25°C unless otherwise specified. Viscosity was measured using a Zahn cup No. 5 manufactured by Rigosha.
[0025] One embodiment of the aqueous matte coating agent of this disclosure is characterized by comprising an emulsified acrylic resin, an emulsified urethane resin, resin fine particles, an aqueous medium, and a curing agent. This matte coating agent provides excellent workability and environmental friendliness, and when the coating film is cured, it can form a matte coating layer with excellent matte properties and adhesion to the substrate.
[0026] Since matte coating agents use an aqueous medium, organic solvents can be reduced or eliminated, and the amount of reactive compounds used can be reduced, improving workability and environmental friendliness. The inclusion of an aqueous medium in the matte coating agent reduces the amount of volatile organic components. In addition, the inclusion of an aqueous medium in the matte coating agent reduces the content of reactive compounds, thus reducing the overall reactivity of the matte coating agent and improving handling. The matte coating agent is applied to the substrate, and a curing reaction proceeds as the aqueous medium is removed to form a coating film. However, because the matte coating agent contains emulsion-type acrylic resin and emulsion-type urethane resin, adhesion to the substrate and abrasion resistance can be obtained even though it is aqueous.
[0027] Furthermore, since the matte coating agent uses an aqueous medium, it can be used to apply a thin film coating to the substrate. When the resulting matte coating layer is thin, resin fine particles protrude from the surface of the matte coating layer, and the resulting uneven shape makes it easier to obtain a matte finish with excellent aesthetic appeal.
[0028] Furthermore, the coating strength of the cured film using emulsion-type acrylic resin, the flexibility of the cured film using emulsion-type urethane resin, and the flexibility of the resin microparticles distributed in the cured film result in a matte coating layer that possesses both abrasion resistance and flexibility, as well as a smooth texture, and a matte finish with excellent aesthetic appeal.
[0029] Furthermore, in addition to the coating strength of the cured film using emulsion-type acrylic resin, the flexibility of the cured film using emulsion-type urethane resin, and the flexibility of the resin fine particles distributed in the cured film, the emulsion-type acrylic resin and emulsion-type urethane resin exhibit hydrophilicity to the extent that they can be emulsified in an aqueous medium. As a result, the surface of the matte coat layer maintains appropriate strength while possessing flexibility, and the occurrence of damage due to repeated friction can be reduced. For example, when multiple laminates are arranged with the matte coat layers overlapping each other, the occurrence of damage due to repeated friction between the matte coat layers can be reduced. Therefore, it is possible to provide laminates with excellent scratch resistance at the consumer use stage and even at the distribution stage.
[0030] <Acid value and hydroxyl value of emulsion-type acrylic resin and emulsion-type urethane resin> The matte coating agent preferably has an acid value of 40 mgKOH / g or less and a hydroxyl value of 20 mgKOH / g or more relative to the total mass of the emulsion-type acrylic resin and emulsion-type urethane resin.
[0031] The acid value (hereinafter also referred to as acid value A1) relative to the total mass of the emulsion-type acrylic resin and emulsion-type urethane resin is preferably 40 mg KOH / g or less, 20 mg KOH / g or less, or 10 mg KOH / g or less. Within these ranges, the water resistance and alcohol resistance of the matte coat layer can be further enhanced while maintaining the stability of the aqueous matte coat agent, and the abrasion resistance can be further improved. The lower limit of the acid value A1 may be 0 mg KOH / g or higher, 1 mg KOH / g or higher, or 5 mg KOH / g or higher, from the viewpoint of the reactivity and stability of the aqueous matte coating agent. Within these ranges, the stability of the aqueous matte coating agent can be further improved. For example, this acid value A1 may be 0-40 mgKOH / g, 1-20 mgKOH / g, or 5-10 mgKOH / g.
[0032] In this disclosure, the acid value of the resin is expressed as the number of milligrams of potassium hydroxide required to neutralize 1 g of the sample. The acid value can be measured according to the method described in JIS K 0070 (1992).
[0033] The acid value A1 can be determined from the acid value of the emulsion-type acrylic resin and the acid value of the emulsion-type urethane resin as follows. Total mass of emulsion acrylic resin: XM Acid value of emulsified acrylic resin: XA Total mass of emulsified urethane resin: YM Acid value of emulsified urethane resin: YA A1=XA×(XM / (XM+YM))+YA×(YM / (XM+YM))
[0034] The hydroxyl value (hereinafter also referred to as hydroxyl value H1) relative to the total mass of the emulsion-type acrylic resin and emulsion-type urethane resin is preferably 20 mg KOH / g or more, 30 mg KOH / g or more, or 40 mg KOH / g or more, from the viewpoint of reactivity with the curing agent. Within these ranges, the film strength of the matte coat layer can be further increased by reaction with the curing agent while maintaining the stability of the aqueous matte coat agent, thereby further improving water resistance and alcohol resistance. Furthermore, abrasion resistance can be further improved. The upper limit of the hydroxyl value H1 may be 100 mg KOH / g or less, 80 mg KOH / g or less, or 60 mg KOH / g or less. Within these ranges, sufficient water resistance and abrasion resistance can be obtained for the matte coating layer.
[0035] In this disclosure, the hydroxyl value is expressed as the number of milligrams of potassium hydroxide required to neutralize the acetic acid needed to acetylate 1 g of a sample. The hydroxyl value can be measured according to the method described in JIS K 0070 (1992). The acid value H1 can be determined from the hydroxyl value of the emulsion-type acrylic resin and the hydroxyl value of the emulsion-type urethane resin as follows. Total mass of emulsion acrylic resin: XM Hydroxyl value of emulsified acrylic resin: XH Total mass of emulsified urethane resin: YM Hydroxyl value of emulsified urethane resin: YH H1=XH×(XM / (XM+YM))+YH×(YM / (XM+YM))
[0036] The acid value of the emulsified acrylic resin (hereinafter also referred to as acid value Aa) may be 1-100 mgKOH / g, 5-50 mgKOH / g, or 10-30 mgKOH / g. The hydroxyl value (hereinafter also referred to as hydroxyl value Ha) of the emulsified acrylic resin may be 20-200 mgKOH / g, 60-170 mgKOH / g, or 80-100 mgKOH / g.
[0037] The acid value of the emulsified urethane resin (hereinafter also referred to as acid value Au) may be 0-50 mgKOH / g, 1-30 mgKOH / g, or 5-10 mgKOH / g. The hydroxyl value (hereinafter also referred to as hydroxyl value Hu) of the emulsified urethane resin may be 10-60 mgKOH / g, 20-50 mgKOH / g, or 30-40 mgKOH / g.
[0038] The absolute difference between the acid value of the emulsion-type acrylic resin and the acid value of the urethane resin is preferably 100 or less, 50 or less, 20 or less, or 10 or less, and preferably 0.1 or more, 1 or more, or 3 or more. Within these ranges, even when two or more resins are used in combination in the matte coating agent, dispersion stability is maintained more stably, the viscosity of the coating agent is improved, and the uniformity of components in the matte coating layer can be further improved.
[0039] <Emulsified acrylic resin> The emulsion-type acrylic resin preferably exhibits hydrophilicity and is soluble or dispersible in aqueous media. The emulsion-type acrylic resin is preferably provided as an aqueous acrylic resin emulsion. An advantage of this aqueous acrylic resin emulsion is that, being an aqueous dispersion, it releases fewer volatile organic compounds (VOCs). Furthermore, the inclusion of the emulsion-type acrylic resin in the aqueous media helps maintain the stability of the matte coating agent. Additionally, the emulsion-type acrylic resin can impart film strength and abrasion resistance to the matte coating layer, particularly improving scratch resistance.
[0040] Emulsified acrylic resins have acrylic monomer constituent units. Furthermore, emulsion-type acrylic resins obtained by copolymerizing styrene monomers, maleic acid monomers, etc., are also preferred.
[0041] Emulsified acrylic resins are preferably those having ionic groups and being aqueous in the presence of an emulsifier and / or a basic compound. The ionic groups may be acidic or basic groups such as carboxyl groups, sulfonic acid groups, phosphoric acid groups, phosphonic acid groups, and quaternary ammonium bases, with acidic groups being preferred and carboxyl groups being particularly preferred. One method for introducing carboxyl groups is to use an ethylenically unsaturated compound having a carboxyl group as a monomer. Examples of ethylenically unsaturated compounds having a carboxyl group include (meth)acrylic acid; carboxyl-containing (meth)acrylates such as 2-(meth)acryloyloxypropyl phthalate, β-carboxyethyl (meth)acrylate, (meth)acrylic acid dimer, and ω-carboxy-polycaprolactone mono(meth)acrylate; polymerizable unsaturated carboxylic acids such as itaconic acid, maleic acid, fumaric acid, and crotonic acid, and their anhydrides. These can be used individually or in combination of two or more.
[0042] Examples of the above acrylic monomers include aromatic group-containing acrylic monomers such as benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxytetraethylene glycol (meth)acrylate, phenoxyhexaethylene glycol (meth)acrylate, and phenyl (meth)acrylate; methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, heptyl (meth)acrylate, and hexyl (meth)acrylate. Acrylic monomers containing linear or branched alkyl groups such as 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, and tetradecyl (meth)acrylate; acrylic monomers containing alicyclic alkyl groups such as cyclohexyl (meth)acrylate and isovonyl (meth)acrylate; acrylic monomers containing fluorinated alkyl groups such as trifluoroethyl (meth)acrylate and heptadecafluorodecyl (meth)acrylate;(meth)acrylamide, N-methoxymethyl-(meth)acrylamide, N-ethoxymethyl-(meth)acrylamide, N-propoxymethyl-(meth)acrylamide, N-butoxymethyl-(meth)acrylamide, N-pentoxymethyl-(meth)acrylamide, N,N-di(methoxymethyl)acrylamide, N-ethoxymethyl-N-methoxymethylmethacrylamide, N,N-di(ethoxymethyl)acrylamide, N-ethoxymethyl-N-propoxymethylmethacrylamide, N,N-di(propoxymethyl)acrylamide, N-butoxymethyl-N-(propoxymethyl)methacrylamide, N,N-di(butoxymethyl)acrylamide, N-butoxymethyl-N-(methoxymethyl)methacrylamide, N,N-di(pentoxymethyl)acrylamide, N-methoxymethyl-N-(pentoxymethyl)methacrylamide, N,N-dimethylaminopropylacrylamide, N,N-diethylaminopropyl Examples include amide group-containing acrylic monomers such as pyracrylamide, N,N-dimethylacrylamide, and N,N-diethylacrylamide; hydroxy group-containing acrylic monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, glycerol mono(meth)acrylate, 4-hydroxyvinylbenzene, 1-ethynyl-1-cyclohexanol, and allyl alcohol; polyethylene oxide group-containing acrylic monomers such as polyethylene glycol monoacrylate (manufactured by Nippon Oil & Fats Co., Ltd., Bremmer PE-90, 200, 350, 350G, AE-90, 200, 400, etc.), polyethylene glycol / polypropylene glycol monoacrylate (manufactured by Nippon Oil & Fats Co., Ltd., Bremmer 50PEP-300, 70PEP-350, etc.), and methoxypolyethylene glycol monoacrylate (manufactured by Nippon Oil & Fats Co., Ltd., Bremmer PME-400, 550, 1000, 4000, etc.).
[0043] Among the above acrylic monomers, it is preferable that one or more are selected from the group consisting of alkyl esters of (meth)acrylic acid, alkylamides of (meth)acrylic acid, and hydroxyalkyl esters of (meth)acrylic acid. The number of carbon atoms in the alkyl group constituting the alkyl ester, etc., is preferably 1 to 18, 2 to 12, or 4 to 8.
[0044] Examples of the styrene monomers mentioned above include styrene, α-methylstyrene, o-methylstyrene, p-methylstyrene, and m-methylstyrene. Examples of maleic acid monomers include maleic anhydride and maleic acid, and may be alkyl esters with 1 to 18 carbon atoms, alkylamides with 1 to 18 carbon atoms, or hydroxyalkyl esters with 2 to 4 carbon atoms. Furthermore, the emulsion acrylic resin may also use other known monomers commonly used as reaction components in emulsion acrylic resins as reaction components.
[0045] Using these reaction components, an emulsion-type acrylic resin can be produced by known manufacturing methods. Furthermore, it can be made aqueous by methods such as using a known emulsifier or polymer protective colloid, or by introducing a carboxyl group into the molecule and neutralizing it with a basic compound. Examples of basic compounds include those exemplified in the production of emulsion-type urethane resin described later, with amine compounds being preferred, and the use of ammonia being preferred. In addition, the emulsion-type acrylic resin is preferably an aqueous emulsion.
[0046] The emulsified acrylic resin may have a weight-average molecular weight (Mw) of 1,000 to 100,000, 5,000 to 80,000, or 10,000 to 50,000. Within these ranges, it is possible to improve coating properties while appropriately maintaining the viscosity of the matte coating agent. The resulting matte coating layer has uniformity and maintains appropriate hardness, further improving substrate adhesion and abrasion resistance.
[0047] The emulsified acrylic resin preferably has a glass transition temperature (Tg) of 10 to 120°C, more preferably 20 to 100°C, even more preferably 30 to 80°C, and particularly preferably 40 to 60°C. Within these ranges, the adhesion and abrasion resistance of the matte coat layer to the substrate can be further improved. A glass transition temperature of 120°C or lower for the emulsified acrylic resin can impart more matte properties to the matte coat layer. A glass transition temperature of 10°C or higher can improve the film strength of the matte coat layer and further improve its abrasion resistance.
[0048] The emulsion-type acrylic resin preferably has an average particle size (mode diameter) of less than 1 μm. For example, the average particle size (mode diameter) of the emulsion-type acrylic resin is preferably between 10 nm and less than 1 μm, between 50 nm and 500 nm, or between 100 nm and 200 nm. Within these ranges, the stability and applicability of the matte coating agent and the uniformity of the matte coating layer can be further improved.
[0049] The average particle size (mode diameter) of emulsified acrylic resin is the volume-based mode diameter measured by dynamic light scattering, and can be measured using, for example, a NanoTrack UPA MicroTrack Bell instrument. A sample of emulsified acrylic resin diluted 500 times with water is recommended. The mode diameter (most frequent value) represents the particle size with the highest frequency of occurrence in the particle size distribution (the same applies below).
[0050] The emulsion-type acrylic resin is preferably present in an amount of 0.5 to 30% by mass, 2 to 25%, 3 to 17%, or 5 to 10% by mass, relative to the total mass of the matte coating agent. Within these ranges, the stability of the matte coating agent and the matte properties and abrasion resistance of the matte coating layer can be further improved.
[0051] [Emulsified urethane resin] The emulsion-type urethane resin preferably exhibits hydrophilicity and is soluble or dispersible in aqueous media. The emulsion-type urethane resin is preferably provided as an aqueous urethane resin emulsion. An advantage of this aqueous urethane resin emulsion is that, being an aqueous dispersion, it releases fewer volatile organic compounds (VOCs). Furthermore, the inclusion of the emulsion-type urethane resin in the aqueous media helps maintain the stability of the matte coating agent. Additionally, the emulsion-type urethane resin can impart flexibility and abrasion resistance to the matte coating layer.
[0052] The emulsion-type urethane resin may be, for example, a urethane resin synthesized from a polyol, a hydroxy acid, and a polyisocyanate, or a urethane resin having urea bonds (urethane urea resin) obtained by extending the chain of a urethane prepolymer having isocyanate groups at the terminals, synthesized from a polyol, a hydroxy acid, and a polyisocyanate, with a polyamine.
[0053] Emulsified urethane resins can be made aqueous by introducing and neutralizing ionic groups into the resin during the reaction of a polyol and a polyisocyanate. The ionic groups may be acidic or basic groups such as carboxyl groups, sulfonic acid groups, phosphate groups, phosphonic acid groups, or quaternary ammonium bases, with acidic groups being preferred and carboxyl groups being particularly preferred.
[0054] One method for introducing carboxyl groups into emulsified urethane resins is to use compounds having active hydrogen that can react with the following anionic groups and isocyanate groups.
[0055] Examples of compounds having active hydrogen that can react with anionic groups and isocyanate groups include dimethylolalkanoates such as 2,2-dimethylolpropionic acid, 2,2-dimethylolbutanoic acid, 2,2-dimethylolbutyric acid, and 2,2-dimethylolvaleric acid; diamine-type amino acids such as glutamine, asparagine, lysine, diaminopropionic acid, ornithine, diaminobenzoic acid, and diaminobenzenesulfonic acid; and monoamine-type amino acids such as glycine, alanine, glutamic acid, taurine, aspartic acid, aminobutyric acid, valine, aminocaproic acid, aminobenzoic acid, aminoisophthalic acid, and sulfamic acid. These may be used individually or in combination of two or more.
[0056] In particular, from the viewpoint of compatibility and reactivity with other urethane raw materials, it is preferable to use 2,2-dimethylolpropionic acid and / or 2,2-dimethylolbutanoic acid. When polyhydroxycarboxylic acid is used in the production of emulsion-type urethane resin, the hydroxyl group reacts with the polyisocyanate to form a urethane bond, but the carboxyl group is poorly reactive with the isocyanate group, so most of it remains as a carboxyl group and is neutralized in the emulsion-type urethane resin, becoming an acid group that converts it to an aqueous solution.
[0057] (Polyol) Polyols do not include hydroxy acids, which will be discussed later. Examples of polyols include polyester polyols, polyether polyols, polylactone polyols, polycarbonate polyols, polyolefin polyols, dimer ols, and hydrogenated dimer ols. These may be used individually or in combination of two or more. The emulsion-type urethane resin preferably contains a constituent unit consisting of at least one polyol selected from polyester polyols, polyether polyols, and polycarbonate polyols. The number-average molecular weight of the polyol is preferably 500 to 5000.
[0058] Polyester polyol The polyester polyol is preferably in a form having a structural unit consisting of a diol containing a dibasic acid and a branched diol. Examples of dibasic acids include sebacic acid, adipic acid, and succinic acid. The branched diol is a form in which at least one hydrogen atom on the carbon of an alkylene glycol has a substituent. Specifically, it is preferable to contain at least one selected from the group consisting of propylene glycol, 3-methyl-1,5-pentanediol, neopentyl glycol, 2-butyl-2-ethyl-1,3-propanediol, and 2-methyl-1,3-propanediol in an amount of 50% by mass or more relative to the total mass of the diol.
[0059] Polyether polyol Examples of polyether polyols include polyethylene glycol, polypropylene glycol, polytrimethylene glycol, polytetramethylene glycol, and copolymers thereof. More preferably, the emulsion-type urethane resin contains constituent units derived from polyethylene glycol. The constituent units derived from polyethylene glycol are preferably present in an amount of 0.1 to 25% by mass, more preferably 2 to 15% by mass, and even more preferably 2 to 10% by mass, based on the total mass of the emulsion-type urethane resin.
[0060] Polycarbonate polyol The polycarbonate polyol is not limited by its manufacturing method or the type of diol that constitutes it, but examples include polycondensates resulting from transesterification reactions between diols and carbonate compounds. Preferably, the polycarbonate polyol is an alicyclic and / or aliphatic polycarbonate diol.
[0061] Examples of diols include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 2-methyl-1,3-propanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 2-methyl-1,8-octanediol, 1,10-decanediol, 2-butyl-2-ethyl-1,3-propanediol, 1,4-butynediol, 2,2,4-trimethyl-1,3-pentanediol, 1,4-cyclohexanedimethanol, diethylene glycol, polypropylene glycol, and dipropylene glycol. These may be used individually or in combination of two or more. The polycarbonate polyol preferably has a diol structure derived from an alkanediol, particularly 1,6-hexanediol.
[0062] Examples of carbonate compounds include dialkyl carbonates, diaryl carbonates, and alkylene carbonates. Specific examples of carbonate compounds include dialkyl carbonates such as dimethyl carbonate, diethyl carbonate, and dibutyl carbonate, diaryl carbonates such as diphenyl carbonate, and alkylene carbonates such as ethylene carbonate. These may be used individually or in combination of two or more.
[0063] (Hydroxy acid) Hydroxy acids are not limited to those listed below, but polyols containing carboxyl groups can be used. Examples include dimethylolalkanoates such as 2,2-dimethylolpropionic acid, 2,2-dimethylolbutyric acid, and 2,2-dimethylolvaleric acid. These may be used alone or in combination of two or more. Hydroxy acids are used in the manufacturing process of aqueous polyurethane resins, and their carboxyl groups are introduced into the resulting polyurethane resin, giving it an acid value. Unreacted carboxyl groups are neutralized to make the resin aqueous.
[0064] (Polyisocyanate) Examples of polyisocyanates include aromatic diisocyanates, aliphatic diisocyanates, and alicyclic diisocyanates. These may also exist as trimers forming an isocyanurate ring structure.
[0065] Examples of aromatic diisocyanates include 1,5-naphthylene diisocyanate, 4,4'-diphenylmethane diisocyanate (MDI), 4,4'-diphenyldimethylmethane diisocyanate, 4,4'-dibenzyli isocyanate, dialkyldiphenylmethane diisocyanate, tetraalkyldiphenylmethane diisocyanate, 1,3-phenylenedi isocyanate, 1,4-phenylenedi isocyanate, and tolylene diisocyanate.
[0066] Examples of aliphatic diisocyanates include butane-1,4-diisocyanate, hexamethylene diisocyanate, isopropyl diisocyanate, methylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, and lysine diisocyanate.
[0067] Examples of alicyclic diisocyanates include cyclohexane-1,4-diisocyanate, xylylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, methylcyclohexane diisocyanate, norbornane diisocyanate, m-tetramethylxylylene diisocyanate, hydrogenated 4,4-diphenylmethane diisocyanate, and dimer isocyanates obtained by converting the carboxyl groups of dimer acids to isocyanate groups. These may be used individually or in combination of two or more.
[0068] Preferably, it is at least one selected from tolylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, m-tetramethylxylylene diisocyanate, xylylene diisocyanate, bis(isocyanatomethyl)cyclohexane, hexamethylene diisocyanate, and trimers of hexamethylene diisocyanate.
[0069] (Polyamines) Compounds that can be used as polyamines include various known amines, such as 2-hydroxyethylpropylenediamine, di-2-hydroxyethylethylenediamine, di-2-hydroxyethylpropylenediamine, 2-hydroxypropylethylenediamine, di-2-hydroxypropylethylenediamine, ethylenediamine, propylenediamine, hexamethylenediamine, 2-methyl-1,5-pentanediamine, isophoronediamine, dicyclohexylmethane-4,4'-diamine, and dimeramines obtained by converting the carboxyl group of a dimer acid to an amino group. These may be used individually or in combination of two or more.
[0070] (Reaction inhibitor) Reaction stoppers can also be used in combination with polyamines. Examples of reaction stoppers include dialkylamines such as di-n-dibutylamine, monoethanolamine, diethanolamine, 2-amino-2-methyl-1-propanol, tri(hydroxymethyl)aminomethane, 2-amino-2-ethyl-1,3-propanediol, N-di-2-hydroxyethylethylenediamine, N-di-2-hydroxyethylpropylenediamine, N-di-2-hydroxypropylethylenediamine, 2-(2-aminoethylamino)ethanol, and other amines having hydroxyl groups, as well as monoamine-type amino acids such as glycine, alanine, glutamic acid, taurine, aspartic acid, aminobutyric acid, valine, aminocaproic acid, aminobenzoic acid, aminoisophthalic acid, and sulfamic acid. These may be used alone or in combination of two or more.
[0071] (Neutralizing agent) To make polyurethane resins aqueous, it is preferable to neutralize carboxyl groups and other ionizable groups in the resin with a basic compound. Examples of basic compounds include sodium hydroxide, potassium hydroxide, ammonia, methylamine, ethylamine, propylamine, butylamine, hexylamine, octylamine, ethanolamine, propanolamine, diethanolamine, N-methyldiethanolamine, dimethylamine, diethylamine, triethylamine, N,N-dimethylethanolamine, 2-dimethylamino-2-methyl-1-propanol, 2-amino-2-methyl-1-propanol, and morpholine. These may be used individually or in combination of two or more. From the viewpoint of water resistance of printed materials and residual odor, triethylamine and ammonia are preferred.
[0072] (synthesis method) Polyurethane resins can be manufactured by known methods as appropriate. Examples include the acetone method, which uses an organic solvent that is inert and hydrophilic to isocyanates, and solvent-free synthesis methods that do not use any solvents. For example, the method described in Japanese Patent Publication No. 2013-234214 can be used as appropriate.
[0073] The emulsified urethane resin may have a weight-average molecular weight (Mw) of 1,000 to 100,000, 5,000 to 80,000, or 10,000 to 50,000. Within these ranges, it is possible to improve coating properties while appropriately maintaining the viscosity of the matte coating agent. The resulting matte coating layer has uniformity and maintains appropriate hardness, further improving substrate adhesion and abrasion resistance.
[0074] The emulsified urethane resin preferably has a glass transition temperature (Tg) of 50 to 120°C, more preferably 60 to 100°C, and even more preferably 70 to 90°C. Within these ranges, the adhesion and abrasion resistance of the matte coat layer to the substrate can be further improved. A glass transition temperature of 120°C or lower for the emulsified urethane resin can impart more matte properties to the matte coat layer. A glass transition temperature of 50°C or higher can impart flexibility to the matte coat layer, further improving its abrasion resistance.
[0075] The emulsion-type urethane resin preferably has an average particle size (mode diameter) of less than 1 μm. For example, the average particle size (mode diameter) of the emulsion-type urethane resin is preferably between 10 nm and less than 1 μm, between 30 nm and 300 nm, or between 30 nm and 100 nm. Within these ranges, the stability and applicability of the matte coating agent, as well as the uniformity of the matte coating layer, can be further improved.
[0076] The average particle size (mode diameter) of emulsified urethane resin is the volume-based mode diameter measured by dynamic light scattering, and can be measured using, for example, a device manufactured by NanoTrack UPA Co., Ltd. or MicroTrack Bell. The sample to be measured should be emulsified urethane resin diluted 500 times with water.
[0077] The emulsified urethane resin is preferably present in an amount of 2-30% by mass, 5-25% by mass, or 10-20% by mass relative to the total mass of the matte coating agent. Within these ranges, the stability of the matte coating agent and the appearance of the matte coating layer can be further improved.
[0078] In some embodiments, by setting the solid content ratio of emulsion-type acrylic resin to emulsion-type urethane resin within a specific range, a matte coat layer with excellent durability and weather resistance can be provided. Specifically, the mass ratio of emulsion-type urethane resin to the total amount of emulsion-type acrylic resin and emulsion-type urethane resin may be 20 to 95% by mass, and is preferably 30 to 90% by mass, 40 to 85% by mass, or 60 to 80% by mass. These solid content ratios allow the matte coat layer to possess sufficient flexibility and hardness, thereby improving its resistance to the external environment.
[0079] In the matte coating agent, the emulsion-type urethane resin and emulsion-type acrylic resin function as binder resins. The matte coating agent may also contain other binder resins, and it is preferable that the other binder resins are aqueous resins. Examples of other aqueous resins include aqueous styrene-maleic acid copolymer resin, aqueous polyester resin, aqueous shellac, aqueous rosin-modified maleic acid resin, aqueous vinyl chloride-vinyl acetate copolymer resin, aqueous chlorinated polypropylene resin, aqueous hydroxyethyl cellulose resin, aqueous hydroxypropyl cellulose resin, aqueous butyral resin, and the like. The total amount of emulsion-type acrylic resin and emulsion-type urethane resin relative to the total mass of the binder resin may be 50% by mass or more, 80% by mass or more, or 90% by mass or more, and may also be 100% by mass.
[0080] <Resin fine particles> The matte coating agent contains resin fine particles. This improves the matte properties of the matte coating layer. These resin fine particles play an important role in providing the matte properties, and their average particle size is preferably 0.1 to 10 μm, more preferably 0.5 to 8 μm, and even more preferably 1 to 5 μm. In particular, a size in the range of 1.5 to 2.5 μm is preferred.
[0081] The average particle size (mode diameter) of resin microparticles is the volume-based mode diameter measured by dynamic light scattering, and can be measured using, for example, a NanoTrack UPA MicroTrack Bell instrument. The sample used for measurement should be resin microparticles diluted 500 times with water.
[0082] The average particle size of the emulsion-type acrylic resin particles and the average particle size of the emulsion-type urethane resin particles are preferably 1-20%, 2-8%, or 4-6%, respectively, when the average particle size of the resin fine particles is set to 100%. When polyolefin wax particles, as described later, are used, the average particle size of the polyolefin wax particles is preferably 0.1-10%, 0.5-5%, or 1-3%, when the average particle size of the resin fine particles is set to 100%.
[0083] Specific examples of resin microparticles include urethane resin microparticles, silicone resin microparticles, melamine resin microparticles, melamine-benzoguanamine resin microparticles, acrylic resin microparticles, acrylic-styrene copolymer resin microparticles, polycarbonate resin microparticles, polystyrene resin microparticles, and benzoguanamine resin microparticles. Examples of acrylic resin microparticles include polymethyl methacrylate resin microparticles. Examples of benzoguanamine resin microparticles include polycondensate microparticles of benzoguanamine and formaldehyde. Furthermore, the resin microparticles may be biodegradable. The resin microparticles may contain trace amounts of inorganic microparticles on their surface and / or inside. The resin microparticles may be used alone or in combination of two or more types. Because the matte properties of matte coating agents can be improved by resin microparticles, they are expected to have applications in a wide range of industrial fields.
[0084] The resin fine particles are preferably present in an amount of 5 to 35% by mass of the total mass of the matte coating agent. More preferably, they are present in an amount of 8 to 20% by mass, and particularly preferably in an amount of 10 to 15% by mass. This is expected to further improve the physical properties of the matte coating agent. Furthermore, the resin fine particles are preferably present in an amount of 40 to 150 parts by mass, 50 to 100 parts by mass, or 60 to 80 parts by mass per 100 parts by mass of the total of the emulsion-type acrylic resin and emulsion-type urethane resin.
[0085] The glass transition temperature (Tg) of the resin microparticles is preferably in the range of -30 to 40°C, more preferably -20 to 30°C, and even more preferably -15 to 25°C. Within this range of glass transition temperatures, the resin microparticles are more likely to protrude from the surface of the matte coat layer, thereby enhancing the matte properties. Furthermore, the flexibility of the resin microparticles can further improve the abrasion resistance of the matte coat layer. Setting the specific resin microparticle content and glass transition temperature as described above is important for improving the stability and applicability of the matte coat agent and for improving the physical properties of the matte coat layer.
[0086] Specific examples of urethane resin microparticles include cross-linked urethane beads such as ART PEARL C-1000 transparent, ART PEARL C-600 transparent, ART PEARL C-400 transparent, ART PEARL C-800, ART PEARL MM-120T, ART PEARL JB-800T, ART PEARL JB-600T, ART PEARL P-800T, and ART PEARL P-400T (manufactured by Negami Kogyo Co., Ltd.).
[0087] Specific examples of silicone resin microparticles include KMP-594, KMP-597, KMP-598, KMP-600, KMP-601, KMP-602 (manufactured by Shin-Etsu Chemical Co., Ltd.), Trefil E-506S, EP-9215 (manufactured by Toray Dow Corning Co., Ltd.), and others.
[0088] Specific examples of melamine resin microparticles include Epostor SS, Epostor S, Epostor FS, Epostor S6, and Epostor S12 (manufactured by Nippon Shokubai Co., Ltd.). Specific examples of melamine-benzoguanamine resin microparticles include Epostor M30 (manufactured by Nippon Shokubai Co., Ltd.).
[0089] Specific examples of acrylic resin fine particles include Epostor MA1002, Epostor MA1004, Epostor MA1006, Epostor MA1010 (manufactured by Nippon Shokubai Co., Ltd.), Toughtick FH-S005, Toughtick FH-S008, Toughtick FH-S010, Toughtick FH-S015, Toughtick FH-S020 (manufactured by Toyobo Co., Ltd.), Chemisnow MX-80H3wT, MX-150, MX-180TA, MX-300, MX-500, MX-1000, MX-1500H, MX-2000, MX-3000 (manufactured by Soken Chemical Co., Ltd.), and ART PEARL J-4P (manufactured by Negami Kogyo Co., Ltd.).
[0090] Specific examples of acrylic-styrene copolymer resin fine particles include Epostor MA2003 (manufactured by Nippon Shokubai Co., Ltd.), FS-102, FS-201, FS-301, MG-451, and MG-351 (manufactured by Nippon Paint Industrial Coatings Co., Ltd.).
[0091] Specific examples of polycarbonate resin fine particles include the fine particles described in Japanese Patent Publication No. 2014-125495, the fine particles obtained by the manufacturing method described in Japanese Patent Publication No. 2011-26471, and the fine particles obtained by the method described in Japanese Patent Publication No. 2001-213970.
[0092] Specific examples of polystyrene-based microparticles include Chemisnow SX-130H, SX-350H, and SX-500H (manufactured by Soken Chemical Co., Ltd.). Specific examples of benzoguanamine resin microparticles include Epostor MS, Epostor M05, and Epostor L15 (manufactured by Nippon Shokubai Co., Ltd.).
[0093] The matte coating agent preferably contains urethane resin fine particles. Since the urethane resin fine particles tend to orient themselves on the surface of the matte coating layer and protrude from the surface to form an uneven shape, they can further impart a matte finish. In addition, because the urethane resin fine particles are flexible, they impart flexibility to the matte coating layer, further improving its abrasion resistance.
[0094] <Polyolefin wax particles> The matte coating agent may contain polyolefin wax particles. By using polyolefin wax particles, matte properties and abrasion resistance can be imparted to the matte coating layer. Examples of polyolefin wax particles include polyethylene wax particles and polypropylene wax particles. The hardness (penetration) of the polyolefin wax particles at 25°C as specified in JIS K2207 is preferably 10 or less, 4 or less, or 2 or less. The average particle diameter (mode diameter) of the polyolefin wax particles is the volume-based mode diameter measured by dynamic light scattering, and is preferably 0.01 to 10 μm, 0.02 to 1 μm, or 0.03 to 0.1 μm. From the viewpoint of enhancing the matte properties of the matte coating layer, it is preferable that it be 0.3 μm or less, or 0.1 μm or less. Furthermore, from the viewpoint of enhancing the matte properties of the matte coating layer, it is preferable that it be 0.01 to 0.1 μm, or 0.01 to 0.05 μm. The average particle diameter of the polyolefin wax particles can be measured using the same procedure as for the resin fine particles described above. When using polyolefin fine particles, it is preferable to use a combination of polyolefin wax particles and urethane fine particles.
[0095] When polyolefin wax particles are used, the amount of polyolefin wax particles is preferably 0.1 to 20% by mass, 1 to 10% by mass, or 3 to 5% by mass relative to the total mass of the matte coating agent. Having 0.1% or more by mass of polyolefin wax particles can further impart surface smoothness to the matte coating layer. Having 20% or less by mass of polyolefin wax particles can further improve the stability and applicability of the matte coating agent. The amount of polyolefin wax is preferably 5 to 100 parts by mass, 10 to 50 parts by mass, or 20 to 40 parts by mass per 100 parts by mass of resin fine particles. Preferably, the amount of polyolefin wax particles is 5 to 60 parts by mass, 8 to 30 parts by mass, or 10 to 20 parts by mass per 100 parts by mass of the total of the emulsion-type acrylic resin and emulsion-type urethane resin.
[0096] Specific examples of polyolefin wax particles include Mipelon XM-220, XM221U, Chemipearl W500 (manufactured by Mitsui Chemicals, Inc.), and Flowbeads LE-1080 (manufactured by Sumitomo Seika Co., Ltd.).
[0097] <Aqueous medium> The matte coating agent contains an aqueous medium. The aqueous medium may contain water, and may be water alone or a mixture of water and an organic solvent. The aqueous medium may constitute 10-90% by mass, 20-80% by mass, or 30-60% by mass relative to the total mass of the matte coating agent. Within these ranges, an appropriate viscosity is maintained during coating, thereby improving workability. Furthermore, the environmental impact can be reduced, and the working environment can be improved.
[0098] The amount of water relative to the total mass of the aqueous medium may be 100% by mass, but if an organic solvent is included, the amount of the organic solvent may be 0.1 to 20% by mass, 0.5 to 15% by mass, 1 to 10% by mass, or 1 to 8% by mass. The organic solvent is preferably a water-soluble organic solvent that forms the same phase in a mixture with the same volume of water at 1 atmosphere and a temperature of 20°C. Examples of water-soluble organic solvents include lower alcohols such as ethanol, n-propanol, and isopropanol, and glycols such as ethylene glycol and propylene glycol.
[0099] It is preferable that the matte coating agent does not contain water-insoluble organic solvents. The amount of water-insoluble organic solvent relative to the total mass of the matte coating agent may be 5% by mass or less, 3% by mass or less, 1.5% by mass or less, or 1% by mass or less, and is preferably 0.5% by mass or less, or 0.1% by mass or less. Within these ranges, the stability of the matte coating agent can be better maintained from the viewpoint of compatibility with aqueous media. As a result, the coating properties are improved, and the film strength of the matte coating layer can be further improved. It is also possible to reduce the environmental impact. The water-insoluble organic solvent is an organic solvent other than the water-soluble organic solvent mentioned above. In particular, it is preferable that the matte coating agent does not contain water-insoluble organic solvents with a solubility in water of 10 g / 100 mL or less, and its content should be within the above range.
[0100] <Surfactants> The matte coating agent may contain a surfactant. The surfactant may be a nonionic surfactant, a cationic surfactant, anionic surfactant, or an amphoteric surfactant, or a combination of two or more of these. Furthermore, the surfactant can function as an antifoaming agent, leveling agent, slip agent, foam suppressant, defoaming agent, etc., in the matte coating agent.
[0101] (Nonionic surfactant) The matte coating agent preferably contains a nonionic surfactant. The nonionic surfactant can improve the coating stability of the matte coating agent and further improve the surface properties of the matte coating layer. Furthermore, the nonionic surfactant can improve the wettability of resin fine particles in the matte coating agent and further improve dispersibility.
[0102] Examples of nonionic surfactants include polyethylene glycol, polypropylene glycol, or copolymers thereof, polyisobutylene glycol, fluorine-based surfactants, silicone-based surfactants, acetylene glycol-based surfactants, and acetylene alcohol-based surfactants.
[0103] The HLB value of the nonionic surfactant may be 15 or less or 13 or less, but is preferably 10 or less, and more preferably 8 or less, 5 or less, or 4 or less. Within these ranges, the surface properties of the matte coat layer can be improved, and the wettability of the resin fine particles in the matte coat agent can be further improved.
[0104] The nonionic surfactant is preferably an acetylene glycol-based surfactant or an acetylene alcohol-based surfactant, and more preferably an acetylene glycol-based surfactant. Examples of acetylene glycol-based surfactants include acetylene glycol and derivatives obtained by adding alkylene oxide to the hydroxyl group of acetylene glycol. Here, the number of carbon atoms in the alkylene group of the alkylene oxide may be 1 to 4 or 2 to 3, and is preferably ethylene oxide. The number of moles of alkylene oxide added may be 1 to 30, 2 to 20, or 5 to 15.
[0105] Acetylene glycol or its derivatives are preferred if they have a symmetrical molecular structure with an acetylene group at the center, from the viewpoint of imparting a moist feel to the matte coat layer and the wettability of resin fine particles. Acetylene glycol or its derivatives are preferred if hydroxyl groups are bonded to two α-carbons of the acetylene group, or if alkylene oxide chains are introduced to two α-carbons, from the viewpoint of imparting a moist feel to the matte coat layer and the wettability of resin fine particles. The number of carbon atoms in the main chain of one of the carbon chains bonded to the acetylene group may be 1 to 12, 2 to 8, or 3 to 4, and some or all of the hydrogen atoms of these carbon chains may have substituents. Preferred acetylene glycol-based surfactants may be 2,4,7,9-tetramethyl-5-decine-4,7-diol, or derivatives in which ethylene oxide is added to the two hydroxyl groups. The HLB value of the acetylene glycol-based surfactant is preferably 1 to 10, and more preferably 2 to 8, 2.5 to 5, or 3 to 4.
[0106] The surfactant is preferably present in a total mass of 0.1-20%, 0.5-10%, or 1-5% relative to the total mass of the matte coating agent.
[0107] The matte coating agent may use a surfactant as an antifoaming agent or slip agent. In this case, the matte coating agent may contain a silicone-based surfactant. When using a silicone-based surfactant, the amount of the silicone-based surfactant should be 0.01 to 5% by mass, 0.05 to 3% by mass, or 0.1 to 2% by mass relative to the total mass of the matte coating agent. Within these ranges, the inclusion of air bubbles in the matte coating layer is suppressed, and the appearance of the matte coating layer can be further improved. Furthermore, slip properties are imparted to the matte coating layer, further improving its abrasion resistance. In addition, within these ranges, the decrease in the stability of the matte coating agent is suppressed, and the coating properties are improved, further improving the appearance of the matte coating layer.
[0108] <Additives> Matte coating agents may optionally contain additives. Examples of additives include leveling agents, UV absorbers, light stabilizers, plasticizers, adhesion aids, defoamers, slip agents, antistatic agents, pH adjusters, and thickeners. These additives are selected according to the properties of the matte coating agent, and each plays a specific role. Thickeners can be used to adjust the viscosity of the matte coating agent to a range suitable for the printing method. These additives may be included in the matte coating agent as appropriate, and their content may be adjusted as appropriate according to their function. If additives are included, the amount of the additive may be 0.1 to 20% by mass, 0.5 to 10% by mass, or 1 to 5% by mass relative to the total mass of one liquid or the matte coating agent.
[0109] <Hardening agent> The curing agent can crosslink emulsion-type urethane resin and emulsion-type acrylic resin to increase the strength of the coating film. The curing agent is preferably a compound that can react with the hydroxyl groups present in the emulsion-type urethane resin and emulsion-type acrylic resin, respectively. Examples include compounds having two or more crosslinkable groups such as isocyanate groups, blocked isocyanate groups, amino groups, epoxy groups, and carbodiimide groups. In particular, from the viewpoint of reactivity with hydroxyl groups, it is preferable to include an isocyanate-based curing agent, and for example, polyisocyanate-based curing agents and blocked polyisocyanate-based curing agents can be included.
[0110] Examples of isocyanate-based curing agents include aromatic polyisocyanates, aliphatic polyisocyanates, alicyclic polyisocyanates, dimers or trimers of these polyisocyanate compounds, and prepolymers obtained using these polyisocyanate compounds.
[0111] Examples of isocyanate-based curing agents include aromatic isocyanate-based curing agents such as m-phenylenediisocyanate, p-phenylenediisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, 3,3'-dimethyl-4,4'-biphenylenediisocyanate, 3,3'-dimethoxy-4,4'-biphenylenediisocyanate, 3,3'-dichloro-4,4'-biphenylenediisocyanate, 1,5-naphthalenediisocyanate, 1,5-tetrahydronaphthalenediisocyanate, xylylenediisocyanate, and tetramethylxylylenediisocyanate; and tetramethylenediisocyanate, 1,6-hexamethylenediisocyanate, dodecamethylenediisocyanate, and trimethylhexamethylenediisocyanate. Examples of curing agents include aliphatic isocyanate curing agents such as 1,3-cyclohexylene diisocyanate, 1,4-cyclohexylene diisocyanate, hydrogenated xylylene diisocyanate, lysine diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, and 3,3'-dimethyl-4,4'-dicyclohexylmethane diisocyanate; alicyclic isocyanate curing agents such as cyclohexane-1,4-diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, 1,3-bis(isocyanate methyl)cyclohexane, methylcyclohexane diisocyanate, and norbornane diisocyanate; and adduct-type isocyanate curing agents, which are adducts of the above isocyanate curing agents with polyhydric alcohols. Furthermore, the use of isocyanurate-modified curing agents, which are modified isocyanate-based curing agents, is also preferable.
[0112] Examples of polyhydric alcohols used in adduct-side isocyanate curing agents include 1,2-propylene glycol (divalent), diethylene glycol (divalent), dipropylene glycol (divalent), 1,3-butanediol (divalent), neopentyl glycol (divalent), trimethylolpropane (trivalent), 2,2,4-trimethyl-1,3-pentanediol (trivalent), polyethylene glycol (polyvalent), and polypropylene glycol (polyvalent).
[0113] Commercially available isocyanate-based curing agents can be used, such as 24A-100, 22A-75, TPA-100, TSA-100, TSS-100, TAE-100, TKA-100, P301-75E, E402-808, E405-70B, AE700-100, D101, D201, A201H (manufactured by Asahi Kasei), Mytec Y260A (manufactured by Mitsubishi Chemical Corporation), Coronate HX, Coronate HL, Coronate L (manufactured by Nippon Polyurethane Co., Ltd.), and Desmodul N75MPA / X (manufactured by Bayer AG).
[0114] As a blocked polyisocyanate-based curing agent, for example, a compound obtained by blocking the isocyanate group of the above-mentioned polyisocyanate compound with various blocking agents can be used.
[0115] The curing agent may be included in an amount of 0.1 to 20% by mass, 0.5 to 15% by mass, 2.5 to 10% by mass, or 4.5 to 8% by mass, relative to the total mass of the matte coating agent. Within these ranges, the abrasion resistance of the matte coating layer can be further improved. It is more preferable that an isocyanate-based curing agent is included within these ranges.
[0116] In the matte coating agent, the amount of curing agent may be 1 to 50 parts by mass, 5 to 40 parts by mass, or 10 to 30 parts by mass per 100 parts by mass of the total amount of emulsion-type urethane resin and emulsion-type acrylic resin. Within these ranges, the abrasion resistance of the matte coating layer can be further improved. It is more preferable that isocyanate-based curing agents are included within these ranges.
[0117] The curing agent is provided as a second liquid and may be provided separately from at least the emulsion acrylic resin, emulsion urethane resin, and resin fine particles. For example, the matte coating agent may provide the other components excluding the curing agent as a first liquid, and the curing agent as a second liquid. Preferably, the emulsion acrylic resin, emulsion urethane resin, and resin fine particles may be provided as the first liquid, and the curing agent as the second liquid. The second liquid may consist only of the curing agent, but may also contain some or all of the aqueous medium.
[0118] In some embodiments, the solid content of the first liquid may be 10-90% by mass, 20-80% by mass, or 40-70% by mass. Here, the solid content of the first liquid is the mass ratio of the dry film obtained by coating the first liquid to the amount of the first liquid applied.
[0119] In some embodiments, the second liquid may be solvent-free and may contain an isocyanate-based curing agent and optional additives. The second liquid may optionally contain an aqueous medium.
[0120] In some embodiments, the solid content of the matte coating agent may be 10-90% by mass, 20-80% by mass, or 40-70% by mass. Here, the solid content of the matte coating agent is the mass ratio of the cured film obtained by applying the matte coating agent to the amount of matte coating agent applied. In this disclosure, the solid content refers to the total mass of non-volatile components in the matte coating agent.
[0121] <Viscosity> The viscosity of the matte coating agent is preferably 5 to 60 seconds, and more preferably 5 to 30 seconds, when measured using a Zaan Cup No. 5 manufactured by Rigosha with the liquid temperature adjusted to 25°C. Having this viscosity range effectively suppresses excessive penetration of the matte coating agent into the paper substrate after application. Furthermore, it is possible to form a uniform film on the surface of the cured layer, preventing uneven appearance such as streaks. In addition, it is possible to improve the quality of laminates having a matte coating layer made of the matte coating agent and enhance the commercial value of the product.
[0122] <Average particle size of matte coating agent> The average particle size of the matte coating agent is preferably 0.1 to 10 μm, more preferably 0.5 to 8 μm, and even more preferably 1 to 5 μm. Within these ranges, the stability and applicability of the matte coating agent, the uniformity of the matte coating layer, and the gloss value and abrasion resistance of the laminate can be further improved.
[0123] The average particle size of the aqueous matte coating agent is determined by diluting the aqueous matte coating agent 500 times with water, measuring approximately 5 ml of the diluted solution using dynamic light scattering (measurement device: NanoTrack UPA Co., Ltd., MicroTrack Bell Co., Ltd.), and taking the particle size of the peak with the largest particle size from the obtained volume-based particle size distribution data (histogram) as the particle size of the aqueous matte coating agent.
[0124] The method for manufacturing the matte coating agent is not particularly limited. For example, one method involves preparing the first and second liquids separately and mixing them immediately before or several hours before coating. One example of a method for manufacturing the first liquid is to mix an emulsified acrylic resin, an emulsified urethane resin, resin fine particles, and an aqueous medium all at once or in stages. Mixing can be done by stirring with a disper. The stirring time should be between 30 minutes and 3 hours. Furthermore, to improve mixing efficiency and obtain viscosity uniformity, stirring may be done using a roller mill, ball mill, pebble mill, attritor, sand mill, etc.
[0125] If the first liquid contains air bubbles or unexpectedly large particles, these can degrade the quality of the printed material, so it is preferable to remove them by filtration or other means. Conventional filters can be used.
[0126] The method for producing the second liquid is not particularly limited. As an example of a method for producing the second liquid, the components including the curing agent may be mixed together or separately, and the second liquid may be produced by optionally filtering or otherwise performing other methods.
[0127] The matte coating agent may be a one-component, aqueous matte coating agent containing all components, either mixed together or separated. In this case, a blocked polyisocyanate-based curing agent is preferably used.
[0128] <Laminate> According to one embodiment of this disclosure, a laminate can be provided comprising a substrate and a matte coat layer, wherein the matte coat layer is a cured layer of the aqueous matte coat agent according to the embodiment described above. According to another embodiment, a laminate can be provided comprising a substrate, a matte coat layer, and a printed layer formed between the substrate and the matte coat layer, wherein the matte coat layer is a cured layer of the aqueous matte coat agent according to the embodiment described above. These laminates provide excellent substrate adhesion and abrasion resistance, and are therefore expected to have applications in various industrial fields. In a laminate comprising a printed layer between the substrate and the matte coat layer, design aesthetics can be obtained through the printed layer, and it is also possible to create an even stronger laminate.
[0129] A matte coat layer, which is a cured layer, can be formed by heat treatment after printing or coating a substrate with a matte coat agent. In the case of a two-component aqueous matte coat agent, the timing of mixing the first and second liquids can be set appropriately according to the pot life, but it is preferable to do so immediately before or several hours before printing or coating. The heat treatment may be a drying process to remove the aqueous medium, a heating process to form a resin coating film, etc. In these processes, the matte coat agent is heated on the substrate, removing the aqueous medium while the resin component is cured by the curing agent, thereby forming a matte coat layer. The heat treatment should preferably be performed at, for example, 60 to 100°C for a period of time during which curing is sufficiently advanced.
[0130] The thickness of the matte coat layer after curing is usually preferably in the range of 1 to 50 μm. In particular, the range of 1 to 30 μm is more preferred, the range of 1 to 20 μm is even more preferred, the range of 1 to 10 μm is even more preferred, and the range of 1 to 5 μm is especially preferred. By setting the thickness within this appropriate range, the uniformity and durability of the matte coat layer after curing are further improved, and the resin fine particles protrude appropriately from the surface of the cured layer, further improving the matte properties.
[0131] The substrate may be either a permeable or non-permeable substrate, such as a paper substrate or a film substrate. In some embodiments, the laminate is preferably a combination of a paper substrate and a matte coat layer.
[0132] Paper substrates such as ordinary paper or corrugated cardboard are used. While there are no specific requirements for the film thickness of these paper substrates, a range of 0.2 mm to 1.0 mm is preferable. Corona treatment may also be applied to the printed surface. Furthermore, the paper substrate may be coated with a metal such as aluminum to enhance its aesthetic appeal. This metal deposition treatment provides the paper substrate with a high-quality feel and a unique appearance. Surface coating treatments using acrylic resin, urethane resin, polyester resin, polyolefin resin, and other resins are also possible. This improves the durability and water resistance of the paper substrate, making it usable in a variety of environments. In addition to corona treatment, various other surface treatments may be applied, which can improve printability, adhesion, etc. Specific examples include coated cardboard and Mariecoat paper. These are widely used in printing and packaging applications, and the paper substrates provided can meet the diverse needs of users in various forms.
[0133] The film substrate is preferably made of ordinary PET (polyethylene terephthalate), PVC (polyvinyl chloride), etc., and is not particularly limited. A film thickness of 0.02 mm to 1.0 mm is preferably used, and the surface of the substrate may be corona-treated. The film substrate may also be surface-coated with acrylic resin, urethane resin, polyester resin, polyolefin resin, or other resins. Further surface treatments such as corona treatment may also be applied. Examples include Cosmoshine A4300 (manufactured by Toyobo Co., Ltd.), E5101 (manufactured by Toyobo Co., Ltd.), and Crisper K2323 (manufactured by Toyobo Co., Ltd.).
[0134] In some embodiments, the laminate can be suitably used to constitute a packaging material. The laminate may be used alone as a packaging material, or it may be used in combination with other materials. The packaging material may be a packaging container.
[0135] <Method for manufacturing laminates> The method for manufacturing the laminate is not particularly limited, but according to one embodiment of the present disclosure, a method for manufacturing a laminate can be provided which includes the steps of mixing a first liquid and a second liquid to obtain an aqueous matte coating agent, and flexographic printing the aqueous matte coating agent according to the above-described embodiment onto a substrate.
[0136] One example of a method for manufacturing a laminate is to print or coat a matte coating agent onto a substrate, dry it using far-infrared radiation, and then optionally add a heating step to accelerate curing and obtain a matte coating layer. In some cases, it is preferable to repeat this step multiple times. In another example, a printed layer is formed on the substrate using a printing ink composition, a matte coating agent is printed or coated onto the printed layer again, and then a heat treatment is performed to accelerate curing and obtain a matte coating layer. Due to their simplicity and efficient processes, these methods for manufacturing laminates can reduce costs and improve production efficiency.
[0137] The printing and coating methods for matte coating agents are not particularly limited and include, for example, spray, shower, dipping, flow coating, gravure printing, flexographic printing, roll, spin, dispenser, inkjet printing, and screen printing. Among these, gravure printing and flexographic printing are preferred because they allow for high-speed printing.
[0138] Examples of the printing ink compositions used to form the printed layer include known gravure ink compositions, flexographic ink compositions, UV-curable flexographic ink compositions, offset ink compositions, UV-curable offset ink compositions, and other ink compositions. Any of these printing ink compositions may be used, but UV-curable offset ink compositions are preferred.
[0139] Known methods can be used for printing the printing ink composition. Examples include gravure printing, flexographic printing, offset printing, and screen printing. The thickness of the ink layer is preferably 0.1 to 15 μm, and more preferably 0.5 to 12 μm. The printing ink composition may be organic solvent-based, water-based, or an ultraviolet-curable ink composition. Alternatively, the above printing ink compositions may be combined to form the ink layer, which can then be dried or ultraviolet-cured after printing to form the printed layer.
[0140] Since the matte coating agent contains an aqueous medium, it can be used for thin-film coating. Thin-film coating is possible even when using gravure printing and flexographic printing, and even when printing at high speeds. Thin-film coating causes resin microparticles to protrude from the surface of the matte coating layer, forming an uneven surface and providing a more aesthetically pleasing matte finish. Furthermore, because the resin microparticles protrude from the surface of the matte coating layer, which is made flexible by the emulsion-type urethane resin, the abrasion resistance of the matte coating layer can also be improved. The matte coating agent may be applied in multiple layers to form the matte coating layer.
[0141] One example of a method for forming a multi-layer matte coating is to apply a matte coating agent to the substrate to form the first layer, and then apply another layer of matte coating agent to the first layer to form the second layer. Heat curing may be performed after the formation of each layer or only after the formation of the last layer. By applying the matte coating agent as the first layer, followed by a drying step to remove the aqueous medium from the coating film, and then applying the matte coating agent to the uncured or partially cured first layer to form the second layer, the process can be simplified, and the adhesion between the first and second layers can be further improved. Furthermore, with this method, the thin film coating of the second layer makes it easier for resin fine particles to protrude from the surface of the matte coating layer, resulting in a matte finish with superior aesthetic appeal. [Examples]
[0142] The present disclosure will be described in detail below with reference to examples, but the present disclosure is not limited to these examples. In this disclosure, parts and % refer to parts by mass and mass %, respectively, unless otherwise noted.
[0143] (Weight average molecular weight) The weight-average molecular weight was determined by measuring the molecular weight distribution using a GPC (gel permeation chromatography) instrument (HLC-8220, manufactured by Tosoh Corporation) and calculating the converted molecular weight using polystyrene as the standard substance. The measurement conditions are shown below. Columns: The following columns were used, connected in series. TSKgelSuperAW2500 manufactured by Tosoh Corporation TSKgel SuperAW3000 manufactured by Tosoh Corporation TSKgelSuperAW4000 manufactured by Tosoh Corporation TSKgelguard Column Super AWH manufactured by Tosoh Corporation Detector: RI (Differential Refractometer) Measurement conditions: Column temperature 40°C Eluent: Tetrahydrofuran Flow rate: 1.0mL / min
[0144] (Glass transition temperature) The glass transition temperature (Tg) was determined by differential scanning calorimetry (DSC). A Rigaku Corporation DSC8231 was used, with a measurement temperature range of -70 to 150°C, a heating rate of 10°C / min, and the midpoint between the endothermic start temperature and end temperature based on the glass transition in the DSC curve was defined as the glass transition temperature.
[0145] (Acid value) The acid value is the number of milligrams of potassium hydroxide required to neutralize the free fatty acids, resin acids, etc., contained in 1 g of the sample, and was measured by the method described in JIS K 0070.
[0146] (Hydroxyl value) The hydroxyl value is the number of mg of potassium hydroxide equivalent to the hydroxyl groups contained in 1 g of the sample, and was measured by the method described in JIS K 0070.
[0147] (Average particle size of water-based matte coating agent) The average particle size of the aqueous matte coating agent is determined by diluting the aqueous matte coating agent 500 times with water, measuring approximately 5 ml of the diluted solution using dynamic light scattering (measurement device: NanoTrack UPA Co., Ltd., MicroTrack Bell Co., Ltd.), and taking the particle size of the peak with the largest particle size from the obtained volume-based particle size distribution data (histogram) as the particle size of the aqueous matte coating agent.
[0148] (Average particle size of emulsified urethane resin, emulsified acrylic resin, resin microparticles, silica, and polyolefin wax) The average particle size was determined by diluting each particle 500 times with water, and measuring approximately 5 ml of the diluted solution using dynamic light scattering (measurement device: NanoTrack UPA Co., Ltd., MicroTrack Bell Co., Ltd.). The largest peak among the peaks in the obtained volume particle size distribution data (histogram) was defined as the particle size (mode diameter).
[0149] <Manufacturing Example 1: Emulsified Urethane Resin A> In a reaction vessel equipped with a stirrer, thermometer, dropping funnel, and reflux apparatus, 50.0 parts of polycarbonate diol (product name: ETERNACOLL UH-200, manufactured by UBE Corporation, number average molecular weight 1958, hydroxyl value 57.3 mg KOH / g, polycarbonate diol obtained by reacting 1,6-hexanediol with a carbonate ester), 1.7 parts of 2,2-dimethylolpropionic acid, 10.0 parts of dicyclohexylmethane diisocyanate, and 10.0 parts of tetramethylxylene diisocyanate were heated at 80-90°C for 4 hours under a nitrogen atmosphere in the presence of 15.2 parts of dipropylene glycol dimethyl ether and 0.05 parts of dibutylsus laurate. Quantification of residual NCO revealed an OH conversion rate of 98% or more. After the reaction mixture was brought to 80°C, 2.8 parts of triethylamine were added and the mixture was stirred for 30 minutes. Furthermore, this reaction mixture was added to 233.3 parts of water while being vigorously stirred, and then 10.2 parts of 2-(2-aminoethylamino)ethanol was added to obtain emulsified urethane resin A.
[0150] <Manufacturing Examples 2 and 3: Emulsified Urethane Resins B and C> Emulsified urethane resins B and C were obtained in the same manner as emulsion-type urethane resin A, except that the raw materials and mixing ratios listed in Table 1 were changed.
[0151] [Table 1]
[0152] <Manufacturing Example 4: Emulsified Acrylic Resin A> A mixture of 65.0 parts styrene, 11.5 parts n-butyl acrylate, 1.9 parts acrylic acid, 1.5 parts tert-dodecyl mercaptan, 1.4 parts Hythenol NF-08 (manufactured by Daiichi Kogyo Seiyaku), and 40.4 parts ion-exchanged water was pre-mixed and stirred to prepare an emulsion of ethylenically unsaturated monomers. In a reaction vessel equipped with a stirrer, thermometer, dropping funnel, and reflux condenser, 68.9 parts of deionized water and 5% of the emulsion were added. The internal temperature was raised to 80°C and the mixture was thoroughly purged with nitrogen. Then, 2.0 parts of a 5% aqueous solution of potassium persulfate (0.1 parts solids) was added as an initiator to start emulsion polymerization. While maintaining the internal temperature at 80°C, the remaining emulsion and 2.0 parts of a 5% aqueous solution of potassium persulfate (0.1 parts solids) were added dropwise over 3 hours, and the reaction was continued for a further 4 hours. After the reaction was complete, 1.8 parts of 25% aqueous ammonia was added to neutralize the mixture, and the solids content of the aqueous dispersion was adjusted to 30.0% with deionized water to obtain emulsion-type acrylic resin A.
[0153] <Manufacturing Examples 5-7: Emulsified Acrylic Resins B-D> Except for changing the raw materials and mixing ratios listed in Table 2, emulsion acrylic resins B to D were obtained in the same manner as emulsion acrylic resin A.
[0154] [Table 2]
[0155] <Manufacturing Example 8: Water-soluble urethane resin> In a reaction vessel equipped with a stirrer, thermometer, dropping funnel, and reflux apparatus, 240.7 parts of polytetramethylene glycol (number average molecular weight 2000), 12.3 parts of polyethylene glycol (number average molecular weight 2000), 48.4 parts of 2,2-bis(hydroxymethyl)propionic acid, 1.6 parts of 1,4-butanediol, 101.9 parts of isophorone diisocyanate (IPDI), and 101.0 parts of methyl ethyl ketone were charged and reacted at 90°C for 7 hours. Subsequently, 72.3 parts of 2-propanol were added, and then 30 parts of 25% aqueous ammonia and 1157.7 parts of deionized water were gradually added to make the mixture aqueous. After removing methyl ethyl ketone and 2-propanol by vacuum distillation, the solid content was adjusted with deionized water to obtain a water-soluble urethane resin.
[0156] (Example 1) Table 3 shows the formulations of aqueous matte coating agents. In the table, solid content is in mass%, average particle size is in μm, Tg is the glass transition temperature (°C), and acid value and hydroxyl value (OH value) are in mgKOH / g.
[0157] <Preparation of water-based matte coating agent> 60 parts of emulsified urethane resin A, 17 parts of emulsified acrylic resin, 15 parts of urethane resin fine particles A, and as additives, 3 parts of wax, 0.5 parts of defoamer, 1 part of silicone, and 3.5 parts of water were added and mixed, and stirred with a bladed stirrer for 90 minutes. Further, 5.0 parts of isocyanate-based curing agent were added and stirred with a bladed stirrer for 10 minutes to obtain aqueous matte coating agent M1.
[0158] <Fabrication of laminates> Using a sheet-fed printing press "Lithrone 26" (manufactured by Komori Corporation), UV-curable offset ink "FD Carton X Sumi M" (manufactured by Toyo Ink Co., Ltd.) was printed onto a paper substrate, Aurora Coat (coated paper, high gloss type, paper thickness 81 μm, manufactured by Nippon Paper Industries Co., Ltd.), to a black density of 1.75 (measurement instrument: X-RiteeXact (manufactured by X-Rite Corporation), conditions: illuminant D50, standard observer 2°, density status E, no filter), and cured with a UV lamp. The printing speed for the above printing was 8000 sheets / hour, the UV lamps consisted of two air-cooled metal halide lamps and one high-pressure mercury lamp, and the UV lamp intensity for all three lamps was set to 160 W / cm (cumulative light intensity 450 mJ / cm). 2 Next, the FD Carton X Ink M print obtained above was coated with aqueous matte coating agent M1 using the Lithrone 26 flexographic coating unit, dried with an IR lamp, and then the aqueous matte coating agent M1 was applied again in the same manner and dried to obtain laminate L1. The anilox roll of the above coating unit had a trihelical engraving pattern, a line screen count of 300 lines / inch, and a cell volume of 9 ml / m². 2 The following materials were used. Furthermore, during flexographic coating, the printing speed was set to 8000 sheets / hour, the liquid temperature of the water-based matte coating agent M1 was 25°C, and the ambient temperature inside the IR drying oven was controlled to 60-100°C.
[0159] (Examples 2-15, Comparative Examples 1-6) Except for using an aqueous matte coating agent with the components shown in Table 3, aqueous matte coating agents and laminates for Examples 2-15 and Comparative Examples 1-6 were prepared according to the same procedure as in Example 1.
[0160] (component) Details of the components used in each example and comparative example are shown below.
[0161] Urethane resin fine particles A: ART PEARL MM-120T, average particle size 2μm, Tg=22℃, manufactured by Negami Kogyo Co., Ltd. Urethane resin fine particles B: ART PEARL C-1000 transparent, average particle size 3μm, Tg=-13℃, manufactured by Negami Kogyo Co., Ltd. Urethane resin fine particles C: ART PEARL C-800 transparent, average particle size 6μm, Tg=-13℃, manufactured by Negami Kogyo Co., Ltd. Acrylic resin fine particles: ART PEARL J-4P, average particle size 2.2μm, manufactured by Negami Kogyo Co., Ltd. Water-soluble acrylic resin: Joncryl 60J, manufactured by BASF. Silica microparticles: Silosphere C1504, 4 μm, manufactured by Fuji Silicia Chemical Co., Ltd. Wax: Polyolefin wax Hi-Tec S-3121, average particle size 0.04 μm, manufactured by Toho Chemical Industry Co., Ltd. Antifoaming agent: Tegoformex 1488, manufactured by Evonik Japan Co., Ltd. Silicone: Slip agent Tegoglide 496, manufactured by Evonik Japan Co., Ltd. Isocyanate-based curing agent: Aquanate AQ-140, Tosoh Corporation.
[0162] (evaluation) The aqueous matte coating agents and laminates obtained in the examples and comparative examples were evaluated as follows. The evaluation results are shown in Table ★3.
[0163] <Viscosity> The viscosity of water-based matte coating agents M1-M15 and CM1-CM6 was measured. Viscosity was measured using a Zahn cup No. 5 manufactured by Rigosha, with the liquid temperature adjusted to 25°C. The viscosity evaluation criteria are as follows: 5 (excellent): 5 seconds or more and 30 seconds or less 3(Acceptable): More than 30 seconds but less than 60 seconds 1 (Poor): Over 60 seconds The ratings for practical use are 3 and 5.
[0164] <Gloss value> The gloss value of the coating surface was measured for the laminates obtained in the examples and comparative examples. Gloss was measured at an incident angle of 60 degrees. The evaluation criteria are as follows. A MicroTrigloss measuring device manufactured by BYK was used for gloss measurement. 5 (Excellent): Gloss value less than 6 4 (Good): Gloss value between 6 and 8 3 (Acceptable): Gloss value 8 or higher but less than 10 2 (Not acceptable): Gloss value between 10 and 12 1 (Inferior): Gloss value 12 or higher The ratings for practical use are 3, 4, and 5.
[0165] <Gloss difference (before and after abrasion resistance)> Using the above printed material, a friction resistance test was conducted using a JSPS-type friction fastness tester (load 500g, 200 cycles, paper: high-quality paper) manufactured by Tester Industries Co., Ltd. The gloss value of the coating surface was measured, and the difference in gloss before and after the friction resistance test was calculated. The gloss was measured at an incident angle of 60 degrees, using Microtrigloss manufactured by BYK. Gloss value difference = (Gloss value after abrasion resistance test) - (Gloss value before abrasion resistance test) 5 (Excellent): Gloss value difference less than 1 4 (Good): Gloss value difference of 1 or more and less than 3 3 (Acceptable): Gloss value difference of 3 or more and less than 5 2 (Not acceptable): Gloss value difference of 5 or more but less than 10 1 (Inferior): Gloss value difference of 10 or more The ratings for practical use are 3, 4, and 5.
[0166] <Abrasion resistance> Using the above printed material, a friction resistance test was conducted using a JSPS-type friction fastness tester (500g load, 200 cycles, against high-quality paper) manufactured by Tester Industries Co., Ltd., and scratches that occurred on the coating surface were evaluated. 5 (Excellent): Completely undamaged 4 (Good): Damage area is between 1% and less than 3%. 3 (Acceptable): Area of injury is 3% or more but less than 5% 2 (Not acceptable): Damaged area is 5% or more but less than 10% 1 (Inferior): Area of injury is 10% or more. The ratings for practical use are 3, 4, and 5.
[0167] <Alcohol resistance> A commercially available disinfectant (ethanol concentration 75% by volume) was sprayed onto the surface of the printed material, and immediately afterward, a friction resistance test was performed using a Japan Society for the Promotion of Science (JSPS) type friction fastness tester (200g load 20 times, metal width 3), and the area of peeling of the coating was evaluated. 5 (Excellent): Peeling area 0% or more and less than 5% 4 (Good): Peeling area 5% or more but less than 10% 3 (Acceptable): Peeling area 10% or more but less than 25% 2 (Not acceptable): Peeling area 25% or more but less than 50% 1 (Poor): Peeling area 50% or more The ratings for practical use are 3, 4, and 5.
[0168] [Table 3A]
[0169] [Table 3B]
[0170] [Table 3C]
Claims
1. A water-based matte coating agent comprising an emulsified acrylic resin, an emulsified urethane resin, resin fine particles, an aqueous medium, and a curing agent.
2. The aqueous matte coating agent according to claim 1, wherein the acid value is 40 mg KOH / g or less and the hydroxyl value is 20 mg KOH / g or more, relative to the total mass of the emulsion-type acrylic resin and the emulsion-type urethane resin.
3. The emulsion-type acrylic resin, the emulsion-type urethane resin, and the resin fine particles are provided as the first liquid. The aqueous matte coating agent according to claim 1 or 2, wherein the curing agent is provided as a second liquid.
4. The aqueous matte coating agent according to claim 1 or 2, wherein the mass ratio of the emulsion urethane resin to the total amount of the emulsion acrylic resin and the emulsion urethane resin is 30 to 90% by mass.
5. The aqueous matte coating agent according to claim 1 or 2, comprising 30 to 100 parts by mass of the resin fine particles with respect to a total of 100 parts by mass of the emulsion-type acrylic resin and the emulsion-type urethane resin.
6. The aqueous matte coating agent according to claim 1 or 2, wherein the absolute value of the difference between the acid value of the emulsion-type acrylic resin and the acid value of the emulsion-type urethane resin is 100 or less.
7. The aqueous matte coating agent according to claim 1 or 2, wherein the average particle size of the aqueous matte coating agent is 0.1 to 10 μm.
8. The aqueous matte coating agent according to claim 1 or 2, wherein the average particle size of the resin fine particles is 1 to 5 μm.
9. The aqueous matte coating agent according to claim 1 or 2, further comprising polyolefin wax particles.
10. The aqueous matte coating agent according to claim 9, wherein the average particle size of the polyolefin wax particles is 0.3 μm or less.
11. The aqueous matte coating agent according to claim 9, wherein the average particle size of the polyolefin wax particles is 0.1 μm or less.
12. The aqueous matte coating agent according to claim 1 or 2, wherein the curing agent comprises an isocyanate-based curing agent.
13. An aqueous matte coating agent according to claim 1 or 2, for use with paper substrates.
14. A laminate comprising a paper substrate and a matte coat layer, wherein the matte coat layer is a cured film of the aqueous matte coat agent described in claim 1 or 2.
15. A method for manufacturing a laminate, comprising the steps of: mixing a first liquid and a second liquid to obtain an aqueous matte coating agent; and flexographic printing the aqueous matte coating agent onto a substrate, wherein the aqueous matte coating agent is the aqueous matte coating agent described in claim 1 or 2.
Citation Information
Patent Citations
Aqueous coating agent composition
JP2009227707A
Water-based ink compositions for surface printing and articles with printing layer
JP2023087626A
Water-based ink composition, water-based ink, laminate, label, and packaging material
JP7567081B1